Catalytic co-pyrolysis of blended biomass – plastic mixture using synthesized metal oxide(MO)-dolomite based catalyst - Harith, N.; Hafriz, R. S. R. M.; Arifin, N. A.; Tan, Ee Sann; Salmiaton, A.; Shamsuddin, A. H. (Elsevier, 2022)
Co-pyrolysis is one of the best new technologies to utilise excess of plastic waste where the products are generated in the form of oil, gas and char. A selective catalyst is needed to improve the quality of the co-pyrolysis product, in which, oil with low of oxygenated compounds content and high yield of oil are favoured. In this work, Malaysian dolomite was modified by doping with transition metals (Ni/Fe/Ca) at 10 wt% loading using the precipitation method and then compared with a modified commercial catalyst named NiO/ZSM-5 zeolite. Co-pyrolysis was conducted using empty fruit bunch (EFB) and high-density polyethylene (HDPE) at 500 °C operating temperature, 10 cm3/min N2 flow rate, 10 wt% catalyst loading, 1:3 HDPE:EFB ratio and 75 g of feedstock with 60 min of operating time in a stainless-steel fluidised bed reactor. The catalysts were characterised using different analysis methods such as XRD, BET and SEM. The highest gas yield of 68% was obtained by increasing the content of calcium oxide (CaO) in dolomite (in dolomite (CaO/CMD900). For the Fe-doped dolomite (Fe3O4/CMD900), the highest oil yield (10.34 wt%) and a high content oxygenated compounds were obtained. For the Ni-doped dolomite (NiO/CMD900), the oil with the highest hydrocarbon yield (85.32 %) and low oxygenated compound (14.68 %) was obtained. This study confirms that modified dolomite can increase the yield and quality of bio-oil.